Learning to be... singing: A choral music education programme - Milhano, Sandrina (2021)
The purpose of this paper is to share the success story of a choral music education program for children and youth, to discuss its benefits to members, and to relate the results to current best practice and research. Beyond its musical and artistic purposes, the Coral Polifónico Juvenil intended to promote on its members, aged between 10 and 16 years, the development of personal, interpersonal, and social skills. The most important findings are that the musical participation in the choral activity has had very positive impacts on pupil’s perceptions, attitudes and beliefs toward music in general and toward choral music participation at school. The pupils felt important, happy, and more useful as well as appreciated by their colleagues at school, by their families, and their communities. They expressed a sense of responsibility and conscientiousness, with notions of values of persistency and perseverance. Regarding interpersonal benefits, they acknowledged in these activities an excellent chance to relate themselves with others and to enlarge their cultural and musical experiences. The pupils recognized that their participation in the choral activity provided them with opportunities to develop their personal, social, and cultural skills and knowledge, as well as providing them with other professional perspectives.